Delayed psychological morbidity associated with snakebite envenoming. - Shehan S Williams (Public Library of Science (PLoS), 2011)
Introduction The psychological impact of snakebite on its victims, especially possible late effects, has not been systematically studied. Objectives To assess delayed somatic symptoms, depressive disorder, post-traumatic stress disorder (PTSD), and impairment in functioning, among snakebite victims. Methods The study had qualitative and quantitative arms. In the quantitative arm, 88 persons who had systemic envenoming following snakebite from the North Central Province of Sri Lanka were randomly identified from an established research database and interviewed 12 to 48 months (mean 30) after the incident. Persons with no history of snakebite, matched for age, sex, geograpical location and occupation, acted as controls. A modified version of the Beck Depression Inventory, Post-Traumatic Stress Symptom Scale, Hopkins Somatic Symptoms Checklist, Sheehan Disability Inventory and a structured questionnaire were administered. In the qualitative arm, focus group discussions among snakebite victims explored common somatic symptoms attributed to envenoming. Results Previous snakebite victims (cases) had more symptoms than controls as measured by the modified Beck Depression Scale (mean 19.1 Vs 14.4; p<0.001) and Hopkins Symptoms Checklist (38.9 vs. 28.2; p<0.001). 48 (54%) cases met criteria for depressive disorder compared to 13 (15%) controls. 19 (21.6%) cases also met criteria for PTSD. 24 (27%) claimed that the snakebite caused a negative change in their employment; nine (10.2%) had stopped working and 15 (17%) claimed residual physical disability. The themes identified in the qualitative arm included blindness, tooth decay, body aches, headaches, tiredness and weakness. Conclusions Snakebite causes significant ongoing psychological morbidity, a complication not previously documented. The economic and social impacts of this problem need further investigation.